Letermovir Resistance Analysis in a Clinical Trial of Cytomegalovirus Prophylaxis for Hematopoietic Stem Cell Transplant Recipients. (29th November 2019) - Douglas, Cameron M; Barnard, Richard; Holder, Daniel; Leavitt, Randi; Levitan, Diane; Maguire, Maureen; Nickle, David; Teal, Valerie; Wan, Hong; van Alewijk, Dirk C J G; van Doorn, Leen-Jan; Chou, Sunwen; et al.
Abstract: Background: Letermovir (LET), a cytomegalovirus (CMV) deoxyribonucleic acid (DNA) terminase inhibitor, was recently approved for prophylaxis of CMV infection in adult CMV-seropositive recipients of allogeneic hematopoietic stem cell transplantation. Cytomegalovirus genotyping was performed to identify LET-resistance-associated variants (RAVs) among subjects in a Phase 3 trial. Methods: The CMV UL56 and UL89 genes, encoding subunits of CMV DNA terminase, were sequenced from plasma collected from subjects with clinically significant CMV infection (CS-CMVi). Novel variants were evaluated by recombinant phenotyping to assess their potential to confer resistance to LET. Results: Genotyping was successful for 50 of 79 LET subjects with CS-CMVi. Resistance-associated variants (encoding pUL56 V236M and C325W) were detected independently in subjects 1 and 3 who experienced CS-CMVi while receiving LET prophylaxis, and 2 other variants (encoding pUL56 E237G and R369T) were detected >3 weeks after subjects 2 and 3, respectively, had discontinued LET prophylaxis and received preemptive therapy with ganciclovir. Conclusions: The detected incidence of CMV resistance among subjects who received LET as prophylaxis in this Phase 3 trial was low. The LET RAVs that were detected mapped to the CMV UL56 gene at positions associated with reduced susceptibility to LET based on resistance selections in cell culture. Abstract : In a Phase 3 trial of letermovir for cytomegalovirus (CMV) prophylaxis in hematopoietic stem cell transplant recipients, UL56 gene mutations conferring letermovir resistance were identified in 3 subjects among 50 who developed clinically significant CMV infection and had genotyping results.